1987
DOI: 10.1093/ageing/16.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Dementia and Immobility

Abstract: Structured physical and psychiatric assessments were performed on 100 elderly women with dementia admitted to either a geriatric or a geriatric psychiatry unit, and the relationship between physical and mental factors and the ability to transfer was investigated. There was an association between limited mobility and physical and psychiatric evidence of cerebrovascular and cardiac disease; but none between mobility and most measures of degree of dementia, vision, hearing, balance, cerebellar function, position … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Most research has focused on the prevalence and etiology of the disease although there are reports correlating cognition and function in dementia (Aske, 1990;MacLennan, Ballinger, McHarg & Ogston;Reed, Jagust & Seab, 1989;Teunisse, Derix & van Crevel, 1991;Uhlmann, Larson & Buchner, 1987).…”
mentioning
confidence: 99%
“…Most research has focused on the prevalence and etiology of the disease although there are reports correlating cognition and function in dementia (Aske, 1990;MacLennan, Ballinger, McHarg & Ogston;Reed, Jagust & Seab, 1989;Teunisse, Derix & van Crevel, 1991;Uhlmann, Larson & Buchner, 1987).…”
mentioning
confidence: 99%
“…In a study of 100 female in-patients diagnosed as suffering from dementia, no association was found between dementia and a generalised decline in neurological function (MacLennan et al, 1987). Focal neurological damage associated with problems of gait, balance and mobility was more likely to be associated with vascular dementia, it was concluded.…”
Section: Causes Of Dementiamentioning
confidence: 89%
“…Diagnoses were based on the International Classification of Disease Criteria (ICD-9) using the history, psychiatric and physical examinations. Patients were included if, at this stage, they had a Clifton Assessment Procedure information/orientation score of 6 or less (MacLennan et al, 1987). They were given a physical assessment which included information on whether a patient was suffering from cerebrovascular disease, Parkinson's disease or another neurological disorder.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous cross-sectional study we investigated the question of whether senile dementia of Alzheimer type (SDAT) or multi-infarct dementia (MID or arteriosclerotic dementia) were associated with a reduction in mobility (MacLennan et al, 1987). The study identified a strong relationship between psychiatric and physical evidence of cerebrovascular disease and limited mobility but there was none between global tests of mental function and mobility.…”
Section: Introductionmentioning
confidence: 99%